Baseline shock index and baroreflex function in older adults - Kenneth M. Madden; Boris Feldman; Graydon S. Meneilly (Aging and Health Research)
Elevations in shock index (SI), defined as heart rate (HR)/systolic blood pressure (BP) are less discriminative of impending shock in older adults. We hypothesized baroreflex dysfunction as a potential explanation for lower baseline SI in older adults. 52 older adults (29 women, 23 men, age ≥ 65; mean age 77.8 ± 0.9 years) were recruited. SI, the modified shock index (MSI, HR/mean BP), and the age corrected SI (Age * SI) as well as baroreflex function (using the sequence method) was measured at baseline. SI (Standardized β = 0.392, p = 0.005), MSI (Standardized β = 0.385, p = 0.006) and Age * SI (Standardized β = 0.431, p = 0.002) showed significant positive associations with BRSup. Age * SI also showed a significant positive association with BRS (Standardized β = 0.329, p = 0.019). Autonomic dysfunction is associated with lower SI in older adults, potentially masking circulatory instability.ClinicalTrials.gov ID NCT01914133